Game-Based Learning in Problem Solving Method: The Effects on Students’ Achievement - Setyaningrum, Wahyu; Pratama, Loviga Denny; Ali, Mohamad Bilal (International Journal on Emerging Mathematics Education, 2018)
This study compared the effects of game-based learning and textbook on students achievement. A problem solving method was employed in learning processes in the classroom. One hundred and thirteen students of grade eight from three junior high schools in the Province of Yogyakarta, who were selected using convenience sampling, participated in this study. The study employed a quasi experiment with a pretest-posttest control-group design. The data were collected through a pre-test, post-test, and questionnaire. The data were analysed using ANOVA, indicating that the students who were exposed to the game-based learning within problem solving approach significantly outperformed their counterparts who were exposed on the basis of textbook within problem solving. The data from questionnaire revealed that the students preferred game-based learning because they could understand the materials with enjoyable and easily.